Are Older Adults More Optimistic? Evidence From China, Israel, and the United States. (15th March 2021) - Lin, Hongmei; Chang, Yuanqing; Chen, Chao; Ho, Yuen Wan; Xi, Wanyu; Zhang, Xin; Fung, Helene H; Ayalon, Liat
Abstract: Objectives: Optimistic bias refers to the phenomenon that individuals believe bad things are less likely to happen to themselves than to others. However, whether optimistic bias could vary across age and culture is unknown. The present study aims to investigate (a) whether individuals exhibit optimistic bias in the context of coronavirus disease 2019 (COVID-19) pandemic, and (b) whether age and culture would moderate such bias. Method: 1, 051 participants recruited from China, Israel, and the United States took the online survey. Risk perceptions consist of 3 questions: estimating the infected probability of different social distance groups (i.e., self, close others, and nonclose others), the days that it would take for the number of new infections to decrease to zero and the trend of infections in regions of different geographical distances (i.e., local place, other places inside participants' country, and other countries). Participants in China and the United States also reported their personal communal values measured by Schwartz's Value Survey. Results: Results from Hierarchical Linear Modeling generally confirmed that (a) all participants exhibited optimistic bias to some extent, and (b) with age, Chinese participants had a higher level of optimistic bias than the Israeli and U.S. participants. Compared to their younger counterparts, older Chinese are more likely to believe that local communities are at lower risk of COVID-19 than other countries. Discussion: These findings support the hypothesis that age differences in risk perceptions might be influenced by cultural context. Further analysis indicated that such cultural and age variations in optimistic bias were likely to be driven by age-related increase in internalized cultural values.